Pengaruh Kesejahteraan Guru, Lingkungan Kerja dan Hubungan Interpersonal Terhadap Kinerja Guru Aparatur Sipil Negara di SMA Negeri 11 Padang - Santi Restina; Dewi Rahmadanirwati (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine the Influence of Teacher Welfare, Work Environment and Interpersonal Relationships on the Performance of State Civil Apparatus Teachers at SMA Negeri 11 Padang City. The type of research used is quantitative research. The population of the study was all teachers at SMA Negeri 11 Padang City as many as 47 respondents, with sampling using the total sampling method where the entire population will be used as a sample. The data source used is primary data. Data analysis techniques usingSPSS Software Version 24. Based on the research results, it shows that the Teacher Welfare variable has a positive and significant effect on Teacher Performance.State Civil Apparatus. Work Environment has a positive and significant effect on the Performance of State Civil Apparatus Teachers and Interpersonal Relationships have a positive and significant effect on the performance of State Civil Apparatus teachers. Teacher Welfare, Work Environment, Interpersonal Relationships have a positive and significant effect on the Performance of State Civil Apparatus Teachers.